2019
DOI: 10.1002/jbm.a.36613
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating large‐scale three‐dimensional constructs with living cells by processing with syringe needles

Abstract: Three‐dimensional (3D) cell constructs composed only of cells and cell‐secreted extracellular matrix have been attractive biomaterials for tissue engineering technology; however, controlling construct morphology and eliminating dead cells after fabrication remain a challenge. It has been hypothesized that moderate stress could shape constructs and eliminate dead cells. The purpose of this study was to establish an easily available technology for shaping 3D cell constructs and eliminating dead cells postfabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The findings suggested that TEP might regenerate bone tissue directly via the surviving cells attached to it. This suggested that any size and shape of bone defect could be successfully repaired using this simulated periosteal approach without pre-vascularization of constructs, which has been a critical challenge in the area of tissue engineering until now [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggested that TEP might regenerate bone tissue directly via the surviving cells attached to it. This suggested that any size and shape of bone defect could be successfully repaired using this simulated periosteal approach without pre-vascularization of constructs, which has been a critical challenge in the area of tissue engineering until now [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the remaining submucosal layer was treated with a series of chemical decellularization steps, given detergent treatment, lyophilized, and sterilized [19]. Finally, all the samples were freeze-dried at -70°C in a lyophilizer, sealed into hermetic packages, and then sterilized using Co-60 gamma irradiation (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Sis Preparation and Tep Fabricationmentioning
confidence: 99%
“…Moreover, it produces low immune reaction [24].The thickness (100 ± 20 µm) of SIS is lower than the critical value (500 µm), can permit attached cells to survive on diffusion of nutrients from the interstitial fluid in early stage after implanting [25]. Successful bone formation was observed in Group1 and 3 via this TEP approach in this study.The findings suggested that TEP might regenerate bone tissue directly via survived cells attached on it.This hints that any size and any shape of bone defect can successfully repair via mimic peristeal approach without pre-vascularization of constructs, which is a critical challenge in tissure engineering area till now [26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The technology for fabricating 3D cell constructs can be applied to other types of cells as well as the BMSCs and DPSCs described in this review [ 98 , 99 ]. Previously, we reported that 3D cell constructs were fabricated from the fibroblast-like L929 cells [ 98 ]. This study demonstrated a method for eliminating the dead cells from the cell construct using a syringe needle.…”
Section: Further Application Of 3d Cell Constructsmentioning
confidence: 99%